EFFECTIVE METHODS IN TEACHING A FOREIGN LANGUAGE (E Global Congress, 2023)
Nowadays, under the influence of drastic changes of the contemporary world, the institutions of higher education focus on the promotion of equity and quality. Special attention is paid to the cross-border education, because the mobility of students and staff facilitates the “formation” of highly skilled workers in certain specialized areas. The main precondition of a successful implementation of mobility programs is a profound knowledge of foreign languages. The given paper deals with the importance of second language acquisition and outlines the strategies of a successful teaching process. The main emphasis is put on the “enhancement” of students’ motivation (including a good teacher-student rapport) and teaching a language through teaching a culture. The first one is regarded as a key element of a classroom success, while the latter simplifies learners’ comprehension of second language reality.